2022
DOI: 10.1021/acsomega.2c01709
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Induced Elemental Mercury Oxidation in Chemical Looping Combustion of Coal

Abstract: Mercury emission is an important issue during chemical looping combustion (CLC) of coal. The aim of this work is to explore the effects of different flue gas components (e.g., HCl, NO, SO 2 , and CO 2 ) on mercury transformation in the flue gas cooling process. A two-stage simulation method is used to reveal the reaction mechanism of these gases affecting elemental mercury (Hg 0 ) oxidation. Furthermore, using this method, Hg 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Additionally, the reducing gases such as CO, H 2 , and NH 3 will consume lattice oxygen over oxygen carriers, which is unfavorable for Hg 0 oxidation. 97 However, the active substances generated from H 2 S, HCl, and Cl 2 can further promote Hg 0 oxidation. 94,102 The oxidation mechanism of Hg 0 in the presence of H 2 S is shown in Figure 8a.…”
Section: The Adsorption Mechanism Of Mercury Over Oxygen Carriersmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, the reducing gases such as CO, H 2 , and NH 3 will consume lattice oxygen over oxygen carriers, which is unfavorable for Hg 0 oxidation. 97 However, the active substances generated from H 2 S, HCl, and Cl 2 can further promote Hg 0 oxidation. 94,102 The oxidation mechanism of Hg 0 in the presence of H 2 S is shown in Figure 8a.…”
Section: The Adsorption Mechanism Of Mercury Over Oxygen Carriersmentioning
confidence: 99%
“…95,96 In addition, SO 2 , H 2 S, HCl, Cl 2 , and other flue gas components will further affect the reaction performance of Hg 0 over oxygen carriers. 97 Therefore, the reaction mechanism of mercury with the oxygen carrier is systematically discussed through DFT calculations in this section.…”
Section: Reaction Mechanism Of Mercury With Oxygen Carriersmentioning
confidence: 99%
See 2 more Smart Citations
“…The removal efficiency of Hg 0 (g) by CuO@TiO 2 @Al 2 O 3 with oxygen uncoupling ability in CLC was 60.71%. Previously, when evaluating oxygen carriers, it was found that the oxidation efficiency of metal oxides for Hg 0 in a HCl atmosphere was in the following order: Co 3 O 4 (Mn 2 O 3 )>Fe 2 O 3 >CuO­(CeO 2 )>SiO 2 (Al 2 O 3 ), , with the lattice oxygen release in the oxygen carrier playing an important role in the removal of mercury. , Oxygen carriers can effectively reduce the emission of Hg 0 , and the conversion of Hg 0 to Hg 2+ is still possible under high-temperature conditions . Therefore, oxygen carriers with good mercury removal performance need to be further developed to improve the efficiency of Hg 0 oxidation in fuel reactors.…”
Section: Introductionmentioning
confidence: 99%